Building a hook for success - EYAL, Nir (Institutional Knowledge at Singapore Management University, 2021)
Nir Eyal rode the Silicon Valley wave and created the Hook model that keeps customers coming back for more. He sees shades of 2006 Silicon Valley optimism in Singapore